O planejamento estratégico do Grêmio Foot Ball Porto Alegrense e do Sport Clube Internacional através de modelos interpretativos - Ghisleni, Taís Steffenello (2005)
On several business departaments, the strategic planning is becoming very important and the organizations need to know and understant ist methods to get the success in the business environment. This planning is valid for the development of the sporting organizations, because it keeps aminimun of global vision, as of an adequate definition of its goals and national strategies, as well as with the international scenery. It also propotiates that the organization and the efficiency of the ways for the consecution of its aims includes the community y participation of fans and of the society in the decision about where to allocate the resources. This work analizes like the bases of the estrategic planning are described by bryson, Almeida and Roche, and like ares accepted by the professional football of the clubs: Grêmio Foot Ball Porto Alegrense and Sport Clube Internacional of Porto Alegre. The football clubs are before a conflicting situation: on the one hand, the social pressure covered by the legislation, that requires changes; on the other hand, a financial situation the most Brazilian Clubs (run into debt and without cash in hand) allows evident the administrative inefficiency and the resulting of the devaluation of their products ou mark. So, this research develops in middle of a change process of organization and functioning of these organizations, and it s in this context that resides its importance for all interesteds. Whit reference to methodology, this work refers to resource of qualitative nature, classified like descriptive, and that used for the development of its process, the study technique of multi-cases.